The impact of environmental education on the sea turtle conservation in Mazatlán, Sinaloa, Mexico. - Rivas-Villarreal, Paola Karina (2023)
The dynamics of a new segment of tourist activity bases its action on creating a link between the subject, the experience and the environment, these are the most important conditions for the tourist to choose the destination to visit. Environmental education within ecotourism is a strategic tool to promote respect for wildlife. The objective of this work was to develop an analysis of the impact of environmental education on the conservation of sea turtles in Mazatlán, Sinaloa, Mexico throughout three decades of recorded biological data in order to promote sustainable tourism with more socially solid attitudes. In Mazatlán Sinaloa, every year, during the sea turtle nesting season (July-October), numerous ecotourist subjects are interested in these endangered reptiles, in order to help protect and conserve these animals. There are regional and federal government public institutions that have a role in environmental education and wildlife conservation. This work involves the approach of animals on a coastal zone on the beaches with tourist dynamics with anthropocentric predominance with the aim of educating various social actors, where the natural resources that are the object of this investigation are sea turtles called olive ridleys Lepidochelys olivacea (Eschscholtz, 1829). The Mazatlán Aquarium with its sea turtle conservation program has managed to protect 15,103 nests; 1,393,194 eggs; 1,103,006 turtles released; 70.2% survival and 290,188 deaths due to natural disasters and other causes. Tourism supported by environmental education promotes an influence on residents and tourists for the care of the natural heritage of natural resources such as marine turtles. This research is a multidisciplinary analysis of the educational, biological, and sociocultural sciences based on a documentary review with in-depth interviews with key actors. There is a conceptual interpretation where social actors learn about biology, conservation, threats, and respect for wild animal life during their visit to the Sinaloan port.